Life, passion and death of a Peruvian newspaper abroad during the Pacific war. Financing and tours of Federico Larrañaga to rescue El Canal (1881-1883) - Abanto Chani, Julio César (2025)
The newspaper El Canal was founded in Panama in 1881 by the Peruvian consul Federico Larrañaga after the fall of Lima. Its founding was due to an individual initiative, which was justified as an effort that would add to the media strategy to defend President Nicolás de Piérola. But, in the long term it was not a sustainable project because it required permanent financing, but it was difficult to access resources due to the economic and political crisis. The article reconstructs Larrañaga’s efforts to maintain the publication of the newspaper, which initially led him to rely on national funds until he self-financed it with amounts obtained on tours he undertook to Mexico, Venezuela and Central America. We use unpublished sources from various Peruvian archives to reconstruct the itinerary and life history of the newspaper and the attempts to obtain new funds abroad.